THE EFFECT OF VILLAGE FUND ALLOCATION ON THE DEVELOPING VILLAGE INDEX IN EAST SUMBA REGENCY - Dini Ue Mone; Adrianus Kabubu Hudang; Yuniarti Reny Renggo (Utan Kayu Publishing, 2025)
The allocation of village funds aims to support rural development, community empowerment, and to strengthen the capacity of village governance in managing resources and fostering sustainable development. The objective of this study is to examine the effect of Village Fund Allocation (ADD) on the Village Development Index (IDM). The findings of the study indicate that ADD has a positive and significant influence on the Village Development Index